Studi Diskriptif Strategi Media Relations Humas Pemkab Sukoharjo Untuk Menghasilkan Pemberitaan Positif Melalui Media Cetak - Muhammad Rizal, Arofat; , Budi Santoso, S.Sos, M.Si (2016)
Has a role as a source of information on local government policies, public relations requires the mass media to convey information to the public. Running media relation is an attempt to achieve maximum publicity for PR. PR needs to approach the journalists to achieve media relations. The purpose of this research is to know strategy done by PR, mass media sub division of Sukoharjo regency to get positive news through printed media. This research uses descriptive qualitative method by using Miles and Huberman analytical technique. Data obtained from interview to 3 respondent from PR Sukoharjo regency and 3 respondent from printed media journalist who served in the Sukoharjo regency. The result of this research show that PR of Sukoharjo Regency successfully communicate with reporters through a personalized approach, providing easy access to information on the district government, and provide facilities needed related to news reporters. With this approach, 80% publication publicist able to fill local printed media in Sukoharjo district.